Modelagem 2.5D do método eletromagnético marinho de fonte controlada utilizando COMSOL Multiphysics® - MIRANDA, Heverlyn Dyanne Teles de (2018)
In this work, we present the implementation of 2.5D models using the software COMSOL Multiphysics R○to simulate the propagation of the electromagnetic field related to marine controlled source electromagnetic (mCSEM). To validate this approach we compare the amplitude and phase of electric field in-line 𝐸𝑥 against two models. The first model is 1D and its results proved to be satisfactory when compared to the onedimensional analytical solution known in the literature by the implementation of open codes, such as DIPOLE1D.f90. The second and third models are 2D and were compared with results from other two-dimensional programs using different numerical techniques, such as the MARE2D code, based on the finite element method and one based on the finite difference method. After the validation of the method, some studies were made about the influence that bathymetry generates on the signals in mCSEM surveys.